Influence of Consumer Ethnocentrism in Buying Brand Ciao Product - Naufal Alfarazy (Master of Management Diponegoro University, 2022)
In this study the author conducted research on the influence of consumer ethnocentrism in buying ciao brand products, the ciao brand is one of the businesses in the fashion sector that was founded in 2020, from the results of validity and reliability tests it is known that the results are valid and consumer ethnocentrism affects the purchase of ciao products This research is based on the CETSCALE and CEESCALE theories that exist on consumer motivation, with the ultimate goal of this study proposing a strategy using the STEPPS framework to increase the dimensions of consumer ethnocentrism.